Effectiveness of Pharmacist–Physician Collaborative Management for Patients With Idiopathic Pulmonary Fibrosis Receiving Pirfenidone - Satsuma, Yukari; Ikesue, Hiroaki; Kusuda, Kaori; Maeda, Mami; Muroi, Nobuyuki; Mori, Ryobu; Kogo, Mariko; Hirabayashi, Ryosuke; Nagata, Kazuma; Nakagawa, Atsushi; Tachikawa, Ryo; Tomii, Keisuke; et al. (Frontiers in Pharmacology, 2020)
Background: Pirfenidone is an anti-fibrotic agent used to treat patients with idiopathic pulmonary fibrosis (IPF). Managing adverse drug events and ensuring compliance with pirfenidone treatment for a prolonged period are important to reduce the rate of disease progression. To maximize the benefits of pirfenidone treatment, we established and evaluated an ambulatory care pharmacy practice, a model of pharmacist–physician collaborative management, for patients receiving pirfenidone. Methods: We conducted a retrospective chart review of 76 consecutive patients treated with pirfenidone in the Kobe City Medical Center General Hospital, Japan, between January 2012 and January 2019. The first group (61 patients) received pirfenidone treatment as conventional management, whereas the second group (15 patients) started pirfenidone based on collaborative pharmacist–physician management. The drug discontinuation rate and time to drug discontinuation were compared between the groups. To analyze factors associated with pirfenidone discontinuation, we used a multivariate Cox regression analysis to evaluate the baseline characteristics of patients, including those receiving the collaborative management. Clinical outcomes were compared using a propensity score matched analysis. Results: In the collaborative management group, pharmacists made 56 suggestions, including suggestions for supportive care (51 suggestions), to the physicians. Among these suggestions, 52 were accepted by the physicians. The discontinuation rates at 3 [6.7% (1/15) vs. 26.2% (16/61)] and 6 [9.1% (1/11) vs. 36.1% (22/61)] months were lower in the collaborative management group than in the conventional management group. Multivariate analysis revealed that collaborative management [hazard ratio (HR) 0.34, 95% CI 0.08–0.96, p = 0.041] and predicted baseline forced vital capacity <60% (HR 2.13, 95% CI 1.17–3.85, p = 0.015) were significantly associated with pirfenidone discontinuation. The time to drug discontinuation was also significantly longer in the collaborative management group than in the conventional management group (p = 0.034, log-rank test). Propensity score matched analysis confirmed a significant correlation between collaborative management and drug discontinuation time (HR 0.20, 95% CI 0.03–0.84, p = 0.027). Conclusions: We established an ambulatory care pharmacy practice for out-patients with IPF receiving pirfenidone. The results suggest that collaborative management may help prevent pirfenidone discontinuation compared with conventional management.